Complete chloroplast genome sequence and phylogenetic analysis of winter oil rapeseed (Brassica rapa L.) - Wu, Jun Yan (Mitochondrial DNA B Resour, 2021)
Winter oil rapeseed ‘18 R-1’ (Brassica rapa L.) is a new variety that can survive in northern China where the extreme low temperature is −20 °C to −32 °C. It is different from traditional B. rapa and Brassica napus. In this study, the complete chloroplast (cp) genome of ‘18 R-1’ was sequenced and analyzed to assess the genetic relationship. The size of cp genome is 153,494 bp, including one large single copy (LSC) region of 83,280 bp and one small single copy (SSC) region of 17,776 bp, separated by two inverted repeat (IR) regions of 26,219 bp. The GC content of the whole genome is 36.35%, while those of LSC, SSC, and IR are 34.12%, 29.20%, and 42.32%, respectively. The cp genome encodes 132 genes, including 87 protein-coding genes, eight rRNA genes, and 37 tRNA genes. In repeat structure analysis, 288 simple sequence repeats (SSRs) were identified. Cp genome of ‘18 R-1’ was closely related to Brassica chinensis, B. rapa and Brassica pekinesis.